Pial artery and subarachnoid width response to apnoea in normal humans. Issue 9 (September 2015) - Wszedybyl-Winklewska, Magdalena; Wolf, Jacek; Swierblewska, Ewa; Kunicka, Katarzyna; Gruszecki, Marcin; Guminski, Wojciech; Winklewski, Pawel J.; Frydrychowski, Andrzej F.; Bieniaszewski, Leszek; Narkiewicz, Krzysztof
Abstract : Background: Little is known about intracranial pressure (ICP)-cerebral haemodynamic interplay during repetitive apnoea. A recently developed method based on near-infrared transillumination/backscattering sounding (NIR-T/BSS) noninvasively measures changes in pial artery pulsation (cc-TQ) as well as subarachnoid width (sas-TQ) in humans. Method: We tested the complex response of the pial artery and subarachnoid width to apnoea using this method. The pial artery and subarachnoid width response to consecutive apnoeas lasting 30, 60 s and maximal breath-hold (91.1 ± 23.1 s) were studied in 20 healthy volunteers. The cc-TQ and sas-TQ were measured using NIR-T/BSS; cerebral blood flow velocity (CBFV), pulsatility index and resistive index were measured using Doppler ultrasound of the left internal carotid artery; heart rate (HR) and beat-to-beat SBP and DBP blood pressure were recorded using a Finometer; end-tidal CO2 (EtCO2 ) was measured using a medical gas analyser. Results: Apnoea evoked a multiphasic response in blood pressure, pial artery compliance and ICP. First, SBP declined, which was accompanied by an increase in cc-TQ and sas-TQ. Directly after these changes, SBP exceeded baseline values, which was followed by a decline in cc-TQ and the return of sas-TQ to baseline. During these initial changes, CBFV remained stable. Towards the end of the apnoea, BP, cc-TQ and CBFV increased, whereas pulsatility index, resistive index and sas-TQ declined. Changes in sas-TQ were linked to changes in EtCO2, HR and SBP. Conclusion: Apnoea is associated with ICP swings, closely reflecting changes in EtCO2, HR and peripheral BP. The baroreflex influences the pial artery response.